2016
DOI: 10.4103/1319-2442.178253
|View full text |Cite
|
Sign up to set email alerts
|

Influence of nutritional education on hemodialysis patients′ knowledge and quality of life

Abstract: To determine the effects of educational instructions on hemodialysis patients' knowledge and quality of life (QOL), we studied 99 patients randomly assigned to control and experimental groups after participation in a pretest exam. The two groups were not significantly different in terms of demographic composition. The instrument used in this study was a questionnaire regarding patients' knowledge and the standard questionnaire to assess QOL for end-stage renal disease (ESRD) patients. Then, intervention (nutri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 0 publications
3
18
0
3
Order By: Relevance
“…People with low HL may be at increased risk of experiencing psychological distress and difficulty in self-management. This finding is consistent with the results of a study by Dodson et al in Australia and Ebrahimi et al in Iran (13,43). Fraser et al in a systematic review realized that limited HL may represent an important determinant of poor outcomes in CKD, though a better understanding of causal mechanisms and the effectiveness of interventions to address HL is required (44).…”
Section: Discussionsupporting
confidence: 89%
“…People with low HL may be at increased risk of experiencing psychological distress and difficulty in self-management. This finding is consistent with the results of a study by Dodson et al in Australia and Ebrahimi et al in Iran (13,43). Fraser et al in a systematic review realized that limited HL may represent an important determinant of poor outcomes in CKD, though a better understanding of causal mechanisms and the effectiveness of interventions to address HL is required (44).…”
Section: Discussionsupporting
confidence: 89%
“…Some studies have shown positive health outcomes through patient training [40,41]. Advances in information technologies have provided good opportunities to improve the quality of patient training [18,20,[42][43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…(2016) reported that 40--60 min educational sessions lasting 3 months significantly improved the dietary knowledge in the intervention group in HD patients. [12] In another study was done by Duzalan et al . (2018) on HD patients, it was shown that the dietary knowledge post-test scores significantly increased compared with the pretest scores.…”
Section: Discussionmentioning
confidence: 99%